Efficacy and safety of oral Chinese medicine combined with chemotherapy: a systematic review and network meta-analysis - Ma, Yuqi; Li, Jia; Liu, Liyun; Shen, Tao (Frontiers in Pharmacology, 2025)
BackgroundNon-small-cell lung cancer (NSCLC), a leading cause of global cancer mortality, often presents at advanced stages with limited efficacy from standard chemotherapy. This study evaluated the efficacy and safety of six oral traditional Chinese medicines (TCMs) combined with chemotherapy for NSCLC.MethodsFollowing PRISMA-NMA guidelines, a systematic review and network meta-analysis of 36 randomized controlled trials (RCTs, n = 2,846 patients) was conducted. Databases including PubMed, China National Knowledge Infrastructure (CNKI), and Web of Science were searched. Outcomes assessed included objective response rate (ORR), immune markers (CD4–CD8 ratio and natural killer (NK) cells), tumor markers (CA125, carcinoembryonic antigen (CEA), and CYFRA21-1), and adverse events. Data were synthesized using STATA 14.0 and R software, with risk of bias evaluated via the Cochrane RoB 2.0 tool.ResultsCompared to chemotherapy alone, Tongguanteng (TGT, Marsdenia tenacissima) demonstrated superior improvement in the ORR [OR = 1.88, 95% CI: 1.25–2.83]. This effect may be attributable to its vincristine content, which modulates apoptosis through cell-cycle regulation pathways. Huisheng (HS) ranked second in efficacy [OR = 1.34, 95% CI: 1.10–1.61], with its emodin component suppressing NSCLC proliferation via NF-κB pathway inhibition. HS was also associated with improvements in immune markers, including CD4+/CD8+ ratio and NK cell activity. Conversely, TGT significantly reduced tumor markers: CA125, CEA, and cytokeratin-19 fragment (CYFRA21-1). This latter observation may be explained by tenacissoside’s inhibition of cytochrome P450 enzymes (CYP2D6/CYP3A4), which alter drug metabolism. Although TCM–chemotherapy combinations exhibited improved safety profiles compared to chemotherapy alone, the analysis revealed potential publication bias and moderate heterogeneity.ConclusionHS and TGT, potentially through their bioactive components, may enhance chemotherapy efficacy in NSCLC by targeting immune and metabolic pathways. However, these conclusions need further verification. Findings should be interpreted cautiously due to potential bias, limited RCT numbers, and the geographical concentration of studies. Future research should isolate compound-specific effects and validate mechanisms in global trials.